Efficacy of a single low dose of esketamine for patients with irritable bowel syndrome: study protocol for a randomised controlled trial - Lei Jiang; Fang Luo; Yan Xing; Zhe Sun (BMJ Open, 2025)
Introduction As a disorder of gut–brain interaction, irritable bowel syndrome (IBS) is a common reason for patient visits in primary and specialist care settings. IBS is associated with recurrent abdominal pain, altered bowel habit, resulting in alternating constipation and diarrhoea, bloating, without serious organic diseases. The bidirectional relationship between IBS and psychological factor is also complex. Studies have suggested that tricyclic antidepressants can effectively control the concomitant symptoms of IBS, especially some severe and refractory symptoms. At present, the conventional treatment of IBS remains somewhat unsatisfactory. Studies have shown that the antidepressant effects of esketamine are rapid and significant, whether a single low dose of esketamine is effective in IBS deserves further investigation. In this study, we hypothesise that a single low dose of esketamine will be effective for IBS.Methods and analysis This is a single-centre, randomised, double-blind, placebo-controlled trial. Patients with IBS are divided into three levels according to the severity of IBS: mild, moderate and severe. 92 patients in the esketamine group and 92 patients in the control group who are scheduled for colonoscopy will be prospectively recruited in each level. The primary outcome is the IBS Severity Scoring System at baseline and at 3 days, 1 week, 3 weeks, 6 weeks after colonoscopy. The secondary outcome includes IBS-Quality of Life, Bristol Stool Form scale, Hospital Anxiety and Depression Scale, Patient Health Questionnaire-12 Somatic Symptom Score and adverse events. The allocation sequence is assigned by a random number table using a block randomisation method by SPSS (Version 26, IBM Inc., USA) Statistics software. All enrolled patients, anaesthesiologist B and researchers responsible for follow-up and data collection and analysis are therefore fully blinded. All data will be performed using SPSS Statistics software, and a p value <0.05 will be considered statistically significant.Ethics and dissemination The protocol has been approved by the Medical Ethics Committee of Beijing Tiantan Hospital affiliated to Capital Medical University (KY2024-414-02). All participants will sign a written informed consent form. The results will be submitted for publication in peer-reviewed journals, presented at international conferences, and shared with participants via hospital newsletters.Trial registration number Efficacy of Esketamine for Patients With Irritable Bowel Syndrome (NCT06788444).